Signalling the appellative function in a pharmacy sector’s customer magazine / Zur Signalisierung der appellativen Textfunktion in einer Kundenzeitschrift der Apothekenbranche - Breckle, Margit (Kalbotyra, 2012)
Customer magazines are periodically published magazines with instructive and entertaining content, which are published by companies or branches for (potential) customers and which are usually free of charge. In Germany, there are currently more than 3500 customer magazine titles with a total circulation of 456 million copies, which shows the popularity of this communication medium. The most widely spread branch customer magazine Apotheken Umschau reports a monthly circulation of nearly 10 million copies and a range of about 20 million readers. However, customer magazines have hardly been analysed linguistically so far. The article presents a corpus-based study, which deals with textual functions of a pharmacy sector’s customer magazine. In this, the linguistic resources for (in)directly signalling the appellative function are analysed. The corpus consists of ten six to ten-page long, multi-module title issues of the Apotheken Umschau that were published between June and November 2008. The analysis of the title issues reveals a very large variety of linguistic resources which (in)directly signal the appellative function. In the article, the most common grammatical and lexical indicators of the appellative function are presented and illustrated by examples. Additionally, an exemplary quantitative analysis of one title issue is presented. It focuses on how frequently the respective linguistic resources occur and how they are distributed in the texts.